Corrigendum: A Transcriptomic Study Reveals That Fish Vibriosis Due to the Zoonotic Pathogen Vibrio Vulnificus Is an Acute Inflammatory Disease in Which Erythrocytes May Play an Important Role (Front. Microbiol., 2022 13 852677 10.3389/Fmicb.2022.852677) - Reyes-Lopez, F; Vallejos-Vidal, E (Frontiers Media S.A., 2022)
In the original article, we neglected to include the funder “Ministerio de Ciencia e Innovación (MICIN/AEI) (DOI ID: 10.13039/501100011033), PID2020-120619RB-I00 to Carmen Amaro.” The corrected Funding statement appears below: FUNDING This work has been financed by grants AGL2017-87723-P co-funded with FEDER funds) from the Ministry of Science, Innovation, and Universities (Spain) and AICO/2018/123 and AICO/2020/076 from Generalitat Valenciana (Spain). CH-C has been financed by grant BES-2015-073117, an FPI grant fromthe Ministry of Science, Innovation and Universities (Spain). EV-V and FER-L thank the support of Fondecyt iniciación (project number 11221308) and Fondecyt regular (project number: 1211841) (Agencia Nacional de Investigación y Desarrollo (ANID), Government of Chile) grants, respectively. This work was also supported by Ministerio de Ciencia e Innovación (MICIN/AEI) (DOI ID: 10.13039/501100011033), PID2020-120619RB-I00 to CA. The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. © 2022 Hernández-Cabanyero, Sanjuán, Reyes-López, Vallejos-Vidal, Tort and Amaro.